2017
DOI: 10.3389/fmicb.2017.01229
|View full text |Cite
|
Sign up to set email alerts
|

A Genotypic Analysis of Five P. aeruginosa Strains after Biofilm Infection by Phages Targeting Different Cell Surface Receptors

Abstract: Antibiotic resistance constitutes one of the most serious threats to the global public health and urgently requires new and effective solutions. Bacteriophages are bacterial viruses increasingly recognized as being good alternatives to traditional antibiotic therapies. In this study, the efficacy of phages, targeting different cell receptors, against Pseudomonas aeruginosa PAO1 biofilm and planktonic cell cultures was evaluated over the course of 48 h. Although significant reductions in the number of viable ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 90 publications
3
51
0
Order By: Relevance
“…In a study developed by Oechslin et al, the genomic profile of two P. aeruginosa phage-resistant strains was analysed and revealed mutations in genes encoding phage receptors, namely pilT and galU, when compared to the wild-type strain [36]. The same was reported by Pires et al in which the authors described that mutations affecting the galU gene and the pil genes were responsible for bacterial resistance to phages [13 ]. This fact can be a consequence of the endogenous oxidative stress suffered by biofilm cells that leads to DNA damage within biofilms resulting in the development of genetic variants with high adaptability to external conditions [37,38].…”
Section: Development Of Phage Resistant Sub-population Within the Biomentioning
confidence: 61%
See 1 more Smart Citation
“…In a study developed by Oechslin et al, the genomic profile of two P. aeruginosa phage-resistant strains was analysed and revealed mutations in genes encoding phage receptors, namely pilT and galU, when compared to the wild-type strain [36]. The same was reported by Pires et al in which the authors described that mutations affecting the galU gene and the pil genes were responsible for bacterial resistance to phages [13 ]. This fact can be a consequence of the endogenous oxidative stress suffered by biofilm cells that leads to DNA damage within biofilms resulting in the development of genetic variants with high adaptability to external conditions [37,38].…”
Section: Development Of Phage Resistant Sub-population Within the Biomentioning
confidence: 61%
“…It is well known that phages are currently considered as promising antimicrobial agents for biofilm prevention and control [7,8]. Nonetheless, although several studies have reported significant reductions in mono and dual-species biofilms after phage treatment [2,3,[9][10][11][12], the complete eradication of biofilms is an almost impossible task [13 ]. Phages need to reach their host bacteria and attach to specific receptors located at cell surfaces before infection and replication inside their hosts is initiated.…”
Section: Limitations Of Bacteriophages When Used As Anti-biofilm Agentsmentioning
confidence: 99%
“…As expected, higher numbers of resistant colonies emerged at 22 C than at 4 C, with percentages varying between 0 and 33.3% in cells recovered from biofilms formed on polystyrene and 0-100% in cells from SS surfaces, respectively. Since biofilms formed on SS were thicker compared to those formed on polystyrene, cells will be subjected to more stress, and the existence of cellular metabolites and oxygen reactive species surrounding biofilm cells may induce mutations at a higher rate due to the diffusional limitations (Pires et al 2017). At 4 C, most of the surviving cells recovered from polystyrene and SS surfaces as well as from poultry skins (control and pretreatment experiments) were susceptible to all four phages.…”
Section: Discussionmentioning
confidence: 99%
“…The gal T gene is located in the gal gene cluster, which is involved in the metabolism of galactose. Genes of this cluster are widely distributed in various pathogenic agents and these genes have been demonstrated to be associated with the virulence factors such as formation of LPS, CPS, and biofilm formation (Priebe et al, 2004 ; Wong and Akerley, 2005 ; Ramjeet et al, 2008 ; Chai et al, 2012 ; Caboni et al, 2015 ; Meyer et al, 2015 ; Oechslin et al, 2017 ; Pires et al, 2017 ). However, the mechanism of GALT-mediated pathogenesis is still unknown.…”
Section: Introductionmentioning
confidence: 99%